Endobronchial ultrasound-guided transbronchial fine needle aspiration: advantages and potential pitfalls - Hamilton HH; Pellicier J; Bernstein M; Dimashkieh H; Yang J (Dove Medical Press, 2015)
Heidi H Hamilton,1 Jalidsa Pellicier,1 Matthew Bernstein,1 Haytham Dimashkieh,2 Jack Yang1 1Department of Pathology and Laboratory Medicine, Medical University of South Carolina, Charleston, 2Department of Pathology, Greenville Memorial Hospital, Greenville, SC, USA Abstract: Endobronchial ultrasound-guided fine needle aspiration (EBUS-FNA) is currently considered the procedure of choice for evaluating mediastinal and hilar lymph nodes in patients with non-small-cell lung carcinoma. In this setting, it is a minimally invasive procedure that can be used to simultaneously diagnose, stage, and obtain cellular material for ancillary studies. Additionally, EBUS-FNA can also be used to triage and diagnose many other mediastinal pathologic processes, such as metastatic malignancy from nonpulmonary origins, lymphoma, and granulomatous lymphadenopathy. At a time when EBUS-FNA is considered the optimal choice for many neoplastic and nonneoplastic conditions of the mediastinal lymph nodes, it has become increasingly important for pathologists to familiarize themselves with the nuances of this procedure. The primary focus of this review is to explore the advantages, adequacy issues, and potential pitfalls of EBUS-FNA, paying particular attention to the situations that may adversely affect patient management. Keywords: lung cancer staging, cytology, mediastinal lymph node